Structure of the infinitely divisible laws of L — class - Zolotarev, V. M. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Золотарев. Аналитическое строение безгранично делимых законов класса LV. Zolatariovas. Neaprėžtai dalių L — klasės dalių analizinė sandara